A educação pela comunicação como estratégia de inclusão social: o caso da Escola Interativa - Souza, Luciano Simões de (Universidade do Vale do Rio do Sinos, 2006)
This work presents a case study of the “Projeto Escola Interativa”, an experience of education through communication tried by twelve public schools of Salvador (Bahia). The main purpose of Escola Interativa is to contribute for the improvement of the quality of education in the public schools, through the development of educative methodologies that incorporates communication technologies. This investigation had the purpose to describe critically the logic of the communication research field that appears at the Escola Interativa with regard to the development of the capacity to read critically the media messages, the media production experience and the participation on the interactive process through the utilization of the communication technologies, basis of the educative methodology in the researched experience. This study aimed to recognize the articulation of all these elements between themselves and between the social inclusion process of youths from peripheral communities. The analyses produced about t
Keywords: escola inclusiva; inclusão social; jovem carente; meio; tecnologia educacional; educação; mídia; human development and communicacion; media education; Ciências Sociais Aplicadas